Beyond statistics: a new rhetoric for investment theory. Issue 5 (5th August 2014) - Pistorius, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse the current rhetoric of predictability in investment theory. After making the case for unpredictability, a new rhetoric for investment theory is proposed. Design/methodology/approach – McCloskey's project of the rhetoric of economics provides the background and approach for the author's investigation. In particular the author will use the notions of metaphor, prediction, discourse analysis, and virtue ethics. Findings – The current rhetoric equals the original rhetoric in the seminal work of Markowitz. The current rhetoric is based on predictability and rational behaviour. The proposed new rhetoric for investment theory denies predictability. The new rhetoric aims to cope with statistics by stressing that statistics is supportive but not decisive: handling investment theory is about judgements, combining virtues with historical and theoretical insights. Practical implications – The investigation of the rhetoric of investment theory has practical relevance because the theory constitutes investment practice, and can put financial wealth at risk. The new rhetoric for investment theory invites practitioners and researchers to reflect on the epistemology of investment theory, and its consequences for the field. Originality/value – The rhetoric of investment theory is to the author's knowledge not yet analysed in the literature. The rhetorical analysis of the current rhetoric and the proposal of a new rhetoric aim to contribute to the literature on the rhetoric of investment theory.